Surface Engineering and Functional Nanomaterials for Point-of-Care Analytical Devices - Purohit, Buddhadev; Chandra, Pranjal (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book chronicles the role of advanced nanomaterials and surface engineering technologies in the development of point-of-care biosensors for health and environmental monitoring. All aspects of nanomaterial synthesis and characterization, functionalization methods, sensing surface engineering, signal amplification strategies, use of innovative technologies to enhance sensor efficiency and performances, and innovative applications of nanobiosensors to tackle real-life problems are discussed in this book with a focus on optical and electrochemical based sensing. It also covers the detection of infectious diseases and various disease biomarkers, smartphone-based biosensing, and portable diagnostics module developments with a discussion on the working mechanisms of these devices in various domains. The book also illustrates the recent trends in biosensing, and an overview of the challenges and probable solutions for the translation of biosensors from laboratory prototypes to commercial success.
Chapter 1_Advanced surface engineering strategies for point-of-care devices -- Chapter 2_Nanomaterial functionalization strategies for point-of-care devices -- Chapter 3_Advances in two- and three-dimensional nanomaterials for biosensor development -- Chapter 4_Carbon based nanomaterials and their functionalization strategies for biosensing -- Chapter 5_Magnetic nanoparticles based biosensing strategies for clinical analysis -- Chapter 6_Surface Engineered Nanobiosensors for Disease Biomarker Identification -- Chapter 7_Nano-bio-analytical systems for detection of emerging infectious diseases -- Chapter 8_Bioanalytical devices for whole cell and bacteria detection -- Chapter 9_Sensing surface development for volatile organic compound detection -- Chapter 10_Recent trends in enzyme-based sensing devices for clinical analysis -- Chapter 11_Paper based sensing devices for clinical and environmental monitoring -- Chapter 12_Smartphone interface and wearable biosensors for onsite diagnosis -- Chapter 13_Designing aptamers based optical bioanalytical systems -- Chapter 14_Lab-on-a-chip based multiple analytes detection system -- Chapter 15_Commercialization of nanobiosensors: Challenges and opportunities.
Keywords: Molecular probes; Nanobiotechnology; Biomedical engineering; Biological Sensors and Probes; Nanobiotechnology; Biomedical Engineering and Bioengineering